At forlade sekten - Rooke, Tetz (Passage - Tidsskrift for litteratur og kritik, 2009)
Tetz Rooke: “Leaving the Sect” In the prize-winning novel Azazil (2008) by Yusuf Zaydan, a Christian monk tells the dramatic story of his life, which is also the dramatic story of early Christianity in the Middle East. The novel problematizes the role of religion in politics and the individual’s responsibility for violence directed against “non-believers”. The same issues are also addressed in the true life story of the former Egyptian, Islamist activist Khaled al-Berry, Life is More Beautiful than Paradise (2001). Both books show defection as a proper solution when religious movements turn authoritarian and sully both individual freedom and moral principles.